Maternal and neonatal risk factors that predispose to NICU admission: A literature review (Research, Society and Development, 2026)
Introduction: The Neonatal Intensive Care Unit (NICU) is essential for the treatment of life-threatening newborns, promoting the survival and physiological well-being of premature neonates and/or those with associated pathologies. Care begins with quality, humanized prenatal care, facilitating the detection of complications that may affect the pregnancy. Objective: To analyze the maternal and neonatal risk factors that predispose to admission to NICUs. Methodology: This is a narrative literature review using articles from the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL) and the Ministry of Health. The search covered articles published between 2010 and 2022, using descriptors such as “Neonatal Intensive Care Units”, “Gestational age”, “Risk factors”, “Hospitalization units”, “Newborn” and “Maternal behavior”. Discussion: Maternal conditions and the development of the newborn increase the need for admission to the NICU, such as prematurity, low birth weight and severe asphyxia, in addition to maternal factors, including advanced age, high parity, low schooling and unfavorable socioeconomic conditions. Hypertensive syndromes during pregnancy, such as pre-eclampsia, increase the risk of prematurity and low birth weight, as well as complications such as respiratory distress syndrome and neonatal infection, and are another important obstetric risk factor. Conclusion: Preventing scenarios that predispose to admission to the NICU is essential. Therefore, maternal and neonatal risk factors should be managed with adequate prenatal care, thus guaranteeing optimal care possibilities in the current situations.